Implementasi Manajemen Risiko Menggunakan Framework ISO 31000 Pada Usaha NailArt: Studi Kasus "Syarbeauty" di Kota Cimahi - Ghina Aulia Asy-syifa; Maisya Hayina Zahra; Nilam Meylani; Rahma Khairunnisa Amalia; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the implementation of risk management in the micro-enterprise Nail Art “Syarbeauty” in Cimahi using the ISO 31000 framework. As a micro-scale business operating in the beauty sector, Syarbeauty encounters various risks that may affect operational continuity, including market, financial, marketing, operational, human resource, and legal risks. This research employs a descriptive qualitative method through direct observation, in-depth interviews with the business owner, and aliterature review. The identification process resulted in 30 risks, which were then assessed using likelihood and impact scoring. The evaluation revealed one high-level risk, limited capital for business development (R11), twenty medium-level risks such as rapidly changing nail art trends, competition with larger salons, rising operational costs, customer cancellations, and the absence of a business license (NIB); and nine low-level risks including negative online reviews and delays in material supply. The SWOT analysis indicates that Syarbeauty’s strengths lie in service quality and consistent hygiene, while weaknesses include limited digital marketing, unclear branding, and strong dependence on the owner. The application of ISO 31000 significantly supports the business in systematically identifying risks, determining priority treatments, and formulating realistic mitigation strategies to strengthen operational effectiveness and enhance the competitiveness of micro-enterprises in the dynamic nail art industry.